Are All Mutations the Same? A Rare Case Report of Coexisting Mutually Exclusive KRAS and BRAF Mutations in a Patient with Metastatic Colon Adenocarcinoma. (24th July 2017) - Vittal, Anusha; Middinti, Akshay; Kasi Loknath Kumar, Anup
Abstract : 29-year-old Hispanic woman presented to the clinic with complaints of abdominal pain, nausea, fatigue, and constipation. Laboratory tests indicated the presence of iron deficiency anemia and transaminitis. Imaging evaluation revealed marked hepatomegaly with multiple hepatic metastases and pelvic lymphadenopathy. Biopsy of the hepatic lesions showed adenocarcinoma positive for pan-cytokeratin, CMA5.2, villin, and CDX2. She was positive for tumor markers CA 19-9, CA-125, and CEA. Upon further evaluation, she was found to have colorectal cancer positive for KRAS and BRAF mutations. Unfortunately, her disease progressed rapidly and she expired within 3 months from the time of her first diagnosis. KRAS and BRAF mutations are rare enough to be considered virtually mutually exclusive but coexistent mutations appear to be a distinct molecular and clinical subset with aggressive course of illness, which is in dire need of new treatment strategies. Panitumumab and Cetuximab are approved for patients with wild type KRAS CRC. Vemurafenib is a potent inhibitor of the kinase domain in mutant BRAF and its use in BRAF mutated colon cancer remains to be well established. Our report highlights the need to obtain tissue samples from these patients for analysis and to evaluate the benefit of Vemurafenib in colorectal cancers.